Urban heat island in Padua, Italy: Experimental and theoretical analysis. Issue 4 (July 2015) - Noro, M.; Busato, F.; Lazzarin, R.M.
This paper reports the study of the urban heat island (UHI) phenomenon in Padua, a medium size city in the North-East of Italy, one of the most industrialized and developed parts of the country. Data recorded by two fixed meteorological stations (in the centre and out of Padua) during the period 1994–2011 were analysed, showing some increase in the UHI effect during this period. Experimental measurements were carried out during 2012 summer. The main thermo-hygrometric variables (dry-bulb temperature, relative humidity and global solar radiation) were measured by a mobile survey along an exact path, selected in order to cross different zones of the city area: urban, sub-urban and rural. The results indicate the presence of UHI effect in urban zones of the city up to 6 ℃. Some measurements in situ had been carried out in order to evaluate the mean radiant temperature (besides the other meteorological variables) in some characteristic sites of the city area: historic centre, high- and low-density populated residential zones, industrial zone and rural zone. Two simulation models were used to calculate some outdoor comfort indices and to evaluate the effect of some mitigation strategy in characteristic sites of the city.